Efeitos da administração de fentanil na concentração anestésica mínima e nas variáveis cardiorrespiratórias de galinhas (Gallus gallus domesticus) anestesiadas com isofluorano - Rocha, Rozana Wendler da [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The aim of this study was to evaluate the effect of fentanyl on the isoflurane MAC over time and to evaluate the cardiorespiratory effects caused by this association in chickens. The individual isoflurane MAC of seventeen chickens was previously determined using the bracketing method. Hens were anesthetized with isoflurane under controlled ventilation to evaluate the effects of intravenous administration of 10 or 30 μg kg-1 of fentanyl over isoflurane MAC. In the next stage, cardiorespiratory effects of intravenous administration of 30 μg kg-1 of fentanyl were evaluated in seven chickens anesthetized with isoflurane under spontaneous ventilation through up-and-down method. Reduction of MAC was determined using logistic regression in each time interval and the 95 % Wald confidence interval was calculated. Data from physiological variables was analyzed using the Shapiro-Wilk test and RM one way ANOVA followed by the Tukey’s test. Results were considered significant when p < 0.05. At five and 15 minutes after administration of 10 μg kg-1 IV of fentanyl, isoflurane MAC was reduced by 18 % (6.1 to 29.1) e 6 % (-0.6 to 12.9), respectively. Administration of 30 μg kg-1 IV of fentanyl reduced isoflurane MAC by 43 % (13.3 to 71.9) e 13 % (-0.9 to 27.3) at five and 15 minutes, respectively. Cardiorespiratory data of birds anesthetized with isoflurane alone or associated with fentanyl did not differ. Fentanyl reduced dose-dependent the isoflurane MAC after 5 minutes of administration and did not cause significant cardiorespiratory depression in chickens anesthetized under spontaneous ventilation. Its applicability in clinical practice becomes limited since the duration of effect was short.

Objetivou-se determinar o efeito do fentanil sobre a concentração anestésica mínima (CAM) do isofluorano em função do tempo em galinhas e avaliar os efeitos cardiorrespiratórios causados por essa associação. A CAM individual de dezessete galinhas foi previamente determinada pelo método bracketing. Os animais foram anestesiados com isofluorano e mantidos sob ventilação controlada para a avaliação do efeito da administração intravenosa única de 10 ou 30 μg/kg de fentanil sobre a CAM do isofluorano. Na etapa seguinte, foram avaliados os efeitos cardiorrespiratórios decorrentes da associação de 30 μg/kg de fentanil em sete galinhas anestesiadas com isofluorano sob ventilação espontânea, por meio do método up-and-down. A redução da CAM do isofluorano em cada intervalo de tempo foi estimada por meio de regressão logística e o intervalo de confiança de Wald de 95 % foi calculado. Os dados das variáveis fisiológicas foram analisados pelo teste Shapiro-Wilk e ANOVA de uma única via com repetições múltiplas, seguido pelo teste de Tukey. Os resultados foram considerados significativos quando p < 0,05. Aos cinco e 15 minutos após a administração de 10 μg/kg de fentanil a redução da CAM foi de 18 % (6,1 a 29,1) e 6 % (-0,6 a 12,9), respectivamente. A aplicação de 30 μg/kg de fentanil reduziu a CAM em 43 % (13,3 a 71,9) e 13 % (-0,9 a 27,3) aos cinco e 15 minutos, respectivamente. As variáveis cardiorrespiratórias das aves anestesiadas com isofluorano isoladamente ou associado à administração de 30 μg/kg de fentanil não diferiram significativamente. O fentanil reduziu de forma dose-dependente a CAM do isofluorano após 5 minutos da administração e não promoveu depressão cardiorrespiratória significativa em galinhas anestesiadas sob ventilação espontânea. Sua aplicabilidade na rotina clínica torna-se limitada, já que a duração do efeito foi curta.
Effects of fentanyl on the minimum anesthetic concentration and its cardiorespiratory response in isoflurane anesthetized chickens (gallus gallus domesticus)
Keywords: Anestesiologia veterinária; Anestésicos inalatórios; Aves; Monitorização fisiológica; Opioides; Anesthesiology veterinary; Birds; Inhalant anesthetics; Monitoring; Opioids